The Relationship between Students’ MOOC-efficacy and Meaningful Learning - Nordin, Mohamad Sahari (UTM, 2020)
This research explored two important constructs in 21st century e-education—students’ MOOC-efficacy and meaningful learning among undergraduate students in selected public universities in Malaysia. Its main objective was to examine the causal relationship of students’ MOOC-efficacy on meaningful learning. The study conceptualized students’ MOOC-efficacy in four dimensions (i.e. information searching, making queries, MOOC learning, and MOOC usability), while conceiving meaningful learning as having five dimensions (i.e. cooperative learning, active learning, authentic learning, constructive learning, and intentional learning). This research applied cross-sectional survey design. Data were collected with a 52-item questionnaire whose reliability indexes ranged from 0.822 to 0.890 for the dimensions. The study's population was identified as university students who have had some experience with MOOCs and who willingly volunteered to participate in the research. A sample of 603 respondents was drawn through simple random sampling. The full-fledged Structural Equation Modeling (SEM) was adopted for data analysis. The finding indicated that students’ MOOC-efficacy was positively associated with meaningful learning. The results show that students’ MOOC-efficacy explains 67% of the variance in meaningful learning. The fit indices indicate an adequate fit: RMSEA = 0.041, CFI = 0.923 and χ2/df = 2.067. The finding provides further insights into what works in an open online environment. The insights may be used to fulfill learners’ needs and preferences. MOOC-efficacy interventions are crucial in order to encourage students’ meaningful learning in the e-learning platform.